Dinamika Islam Politik Pasca Orde baru: Kajian Psikoanalisi Lacanian atas Hubungan KAMMI dan PKS - Umar, Ahmad Rizky Mardhatillah (ULUL ALBAB Jurnal Studi Islam, 2014)
This article aims at analyzing the relations between student movement andpolitical party in post-reform era of Indonesia. KAMMI, a prominent Islamiststudent movement in Indonesia, often associated with PKS (Prosperous JusticeParty) in terms of identity and political practices. It has created ‘independencedilemma’ for KAMMI because since its first Congress in 1998, this studentorganization has declared ‘independent from all political forces’. This article,using Lacanian psychoanalytical tradition, exposes the forms of KAMMI’ssubjectivity and PKS interpellation that enable this political party to dominateKAMMI’s articulatory practices. The interpellation process is supported withthe projection of fantacy, emotion, and mirror in the development of KAMMIsince 1998 until present. It leads to PKS creating the KAMMI identity andthus made KAMMI’s articulatory practices identical with this party. However,there were several attempts to dislocate the hegemony through several internalreform movements. These attempts, although made contribution to internaldynamics within KAMMI, were unable to create alternative discourse dueto several limits of those movements. The case of KAMMI can be a model toexplain how other student movements develop and relate to political parties inIndonesian post-reform.